2000
DOI: 10.1021/ef990223e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cracking of Athabasca Bitumen:  Influence of Steam on Reaction Chemistry

Abstract: Thermal cracking of Athabasca bitumen at various reaction conditions with and without the presence of steam was investigated to determine if steam has a chemical influence on coking. The reactions were done in 15 mL microautoclave reactors and a 3" diameter fluidized bed coking pilot unit over a range of reaction severity (350-530 °C, 10-60 min reaction time). The differences between reactions with and without steam were investigated by comparing elemental composition of the products and coke yield. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 13 publications
5
49
0
3
Order By: Relevance
“…Vostrikov et al [72] reported the pyrolysis of eicosane in SCW and showed that water accelerated pyrolysis and reacted with a large amount of reaction intermediates. Dutta et al [73] tested the hydrogen exchange from steam to thermally cracked bitumen molecules by doping water with D2O in a temperature range of 623-803 K. They measured the exchanging degrees of three types hydrogen (α-, β-, γ-) in bitumen and found that the α-H were prone to be exchanged with the H of water. Gao et al [74] used D2O as a tracer to study the hydroconversion of Tahe residue in SCW.…”
Section: Mechanisms Of Hydrocarbons Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vostrikov et al [72] reported the pyrolysis of eicosane in SCW and showed that water accelerated pyrolysis and reacted with a large amount of reaction intermediates. Dutta et al [73] tested the hydrogen exchange from steam to thermally cracked bitumen molecules by doping water with D2O in a temperature range of 623-803 K. They measured the exchanging degrees of three types hydrogen (α-, β-, γ-) in bitumen and found that the α-H were prone to be exchanged with the H of water. Gao et al [74] used D2O as a tracer to study the hydroconversion of Tahe residue in SCW.…”
Section: Mechanisms Of Hydrocarbons Transformationmentioning
confidence: 99%
“…The formation of large amounts of coke, through the propagation reactions of radicals, the aggregation of asphaltene, and the addition between activated asphaltene precursors and low molecular radicals or olefins [50,79], not only affects the efficient exploitation of heavy oil, but also brings a series of problems, such as the deactivation of catalysts. Fortunately, the introduction of SCW into heavy oil can effectively reduce the yield of coke [11,[73][74][75]80,81]. To further suppress the formation of coke, many novel SCW processes have been successfully developed.…”
Section: Suppression Of Cokementioning
confidence: 99%
“…Помимо каталитической функции, вода непосредственно участвует в химических реакциях. В [17] показана возможность переноса дейтерия из молекул тяжелой воды в продукты превращения битума при температурах от 350 до 530 ºС, что может свидетельствовать о протекании реакции ингибирования углеводородных радикалов образующихся в ходе термического гомолитического разрыва связей С-С (1)-(3), что также обсуждается в [18,19]:…”
Section: облагораживание тяжелого нефтяного сырья в среде субкритичесunclassified
“…При неката-литическом паровом крекинге присутствие воды по сравнению с термокрекингом практически не сказывается на таких показателях процесса, как выходы кокса и жидких продуктов, глубина обессеривания и др. При этом значительного повышения концентрации оксидов углерода (СО, СО 2 ) в составе газообразных продуктов, что свидетельствовало бы об интенсификации про-текания процессов взаимодействия воды и углеводородов по НТППР либо по другим механиз-мам, не было обнаружено даже при температурах до 480 ºС [17,[93][94][95].…”
Section: каталитический паровой крекинг тяжелого нефтяного сырья в стunclassified
“…The use of H 2 O instead of H 2 in the so called steam cracking has been proposed by several groups as a potential way to upgrade heavy and unconventional oils [4][5][6][7][8]. Hydrothermal heavy oil upgrading has shown important improvements compared to thermal upgrading methods as higher yields to lighter liquid product fractions are obtained at the expense of a reduction in the amount of coke produced [9,10].…”
Section: Introductionmentioning
confidence: 99%